PENGARUH SHOLAT DHUHA TERHADAP PENURUNAN KADAR GLUKOSA DARAH - Rajin, Mukhamad; Mawarti, Herin (Eduhealth, 2010)
AbstractPrayer Dhuha when implemented in a County and tumaâ€™ninah, will be two movements of muscle contraction isometric and isotonic muscular contractions. Movement with isometric and isotonic muscle contraction both can decreaseÂ blood glucose levels. This research aims to prove that Dhuha Prayer can decrease blood glucose levels. This research design uses â€œa randomized control group pre test - post test designâ€, with independent variables is Dhuha Prayer and for the dependent variables is the blood glucose levels. The sample size in this study were 15 respondents respectively for the control and treatment groups. Samples are taken using simple random sampling.Â Statistical test use of SPSS with T-test, with significance level a â‰¤ 0,05. Test results Â of Independent T-testn, beforepraying Dhuha got value Ï = 0.650, whereas after prayers Dhuha got value Ï = 0.000. From these test results, the research concluded that there was an effect of prayer Dhuha with Decreased of blood glucose levels. Based on these results, then Dhuha prayer may be used as an alternative for substitute for exercise therapy in patients with diabetes mellitus. Dhuha Prayer Â has several advantages compared with exercise. However Dhuha prayer should never be used solely because they want to lower the blood glucose level. Prayer intentions simply because GOD and we hand it all to GOD, and the researcher was very confident that with the prayers Dhuha we do with the County ', tuma'ninah and istiqomah because GOD can cure patients with diabetes mellitus.Keywords:Â Dhuha Prayer, Blood Glucose Levels